Effect of hedgerow species in alley cropping systems on surface soil physical properties of an Oxic Paleustalf in southwestern Nigeria - Hulugalle, N.R.; Kang, B.T. (Cambridge University Press, 1990)
Effects of hedgerow species on surface soil physical properties were studied in an on-going trial established since 1981 on an Oxic Paleustalf in southwestern Nigeria. The experimental treatments were Leucaena leucocephala, Gliricidia sepium, Alchornea cordifolia and Acioa barterii hedgerows planted at 4 m interhedgerow spacings and a control (no hedgerows). Plots were sequentia-ly cropped with maize (Zea mays) and cowpea (Vigna unguiculata). Soil physical properties, i.e. particle size distribution, bulk density, apparent pore size distribution and water infiltration, were monitored during the dry season in January and the main growing season in June 1989. Soil temperature was monitored at approximately monthly intervals from February to June 1989. Soil properties of alleycropped plots were superior to those of the control. Soil compaction was highest in the control and lowest with L. leucocephala. Between the hedgerow species, within-season increases in soil compaction were largest with A. cordifolia. Lowest soil temperatures were observed with L. leucocephala and A. barterii. Frequency, quantity and quality of prunings produced by the hedgerow species appeared to have a major beneficial effect on soil physical properties.